Gender Identity Awareness and Inclusion: Developing and Implementing a K-5 Lesson Plan Trajectory to Support All Students - Baxter, Holly; Drescher, Talya; Ballesteros-Sola, Maria (Allies for Education, 2020)
This article explores the process of creating and intitial outcomes of a gender diversity lesson plan trajectory for students in grades kindergarten through fifth in a small California school district. The discussion includes the impetus for the creation of the lessons, some of the challenges faced by the district and methods of overcoming those challenges ultimately resulting in successful implementation. Practical resources are included.